Operation control system of sterilization installation on the basis of the accelerator UELV-10-10-S-70 - Bystrov, P.A.; Pavlov, Yu.S.; Kazyakin, А.А.; Kozlov, A.А. (Вопросы атомной науки и техники, 2019)
The design of the system for monitoring and recording the operating parameters of the radiation installation at the IPCE RAS on the basis of the accelerator UELV-10-10-S-70 is presented. Solutions are proposed for collecting data from the equipment of the sterilization installation and the accelerator, their primary analysis, transfer to the computer for further processing and fixation in the journal. Presented software of the control device. The created device allows you to timely identify and prevent the occurrence of emergency situations. Представлено конструкцію системи контролю та реєстрації параметрів роботи радіаційної технологічної установки ІФХЕ РАН на базі прискорювача УЕВЛ-10-10-С-70. Запропоновано рішення для збору даних з устаткування стерилізаційної установки і прискорювача, їхнього первинного аналізу, передачі на ЕОМ з метою їхньої подальшої обробки і фіксації в журналі. Представлено програмне забезпечення пристрою контролю. Створений пристрій дозволяє вчасно виявити, а також попередити виникнення позаштатних ситуацій. Представлена конструкция системы контроля и регистрации параметров работы радиационной технологической установки ИФХЭ РАН на базе ускорителя УЭЛВ-10-10-С-70. Предложены решения для сбора данных с оборудования стерилизационной установки и ускорителя, их первичного анализа, передачи на ЭВМ с целью их дальнейшей обработки и фиксации в журнале. Представлено программное обеспечение устройства контроля. Созданное устройство позволяет своевременно выявить, а также предупредить возникновение нештатных ситуаций.